Efeito do armazenamento em água na resistencia de União de diferenets abordagens de adesão a dentina - Martins, Gislaine Cristine (2008)
The purpose of this study was to evaluate the effects of water storage on resindentin bond strengths [μTBS] formed by different adhesive bonding approaches. A flat superficial dentin surface the 24 human third molars were exposed and polished to create a standardized smear layer. The teeth were randomly distributed into four different: total-etch 3 step (Adper™ Scotchbond™ Multi-Purpose, 3M ESPE - SBMP), and total-etch 2 step (Adper™ Single Bond 2, 3M ESPE - SB); self-etch 2 step (AdheSE, Ivoclar/Vivadent - AD); and self-etch 1 step (Adper™ Prompt™ LPop ™, 3M ESPE - LP). Following the adhesive application (n=6), resin composite crowns were incrementally placed (Filtek™ Supreme XT - 3M ESPE) in order to obtain bonded sticks, with a cross-sectioned area of about 0,8 mm2. The bonded sticks were randomly divided and assigned to be tested immediately [IM] (n=30) or after 6 months of water storage [6M](n=30). Two-way ANOVA and Tukey’s test showed that none of the adhesives showed degradation after 6 months, except SB, which was the one that achieved the highest μTBS either in the immediate time (49.13 MPa) and after 6 months (40.27 MPa). LP showed the lowest μTBS in both periods of evaluation (18.35 and 18.34 MPa). AD and SBMP showed intermediate performance. But the SB showed lower μTBS significantly after storage anyway showed high results. Conclusion: Although a significant degradation was only observed for SB, this was the adhesive that showed the highest μTBS after 6M of water storage. It seems that the microtensile test is not sensitive to detect degradation for adhesives with low immediate μTBS.